(Perservation of salted Press-Boiled Milk Fish (Chanos chanos) by Packaging Method) - Sutrisniati, Dwi; Yulistia, Aan; Astuti, Juli (Balai Besar Industri Agro, 1987)
A study on the preservation of salted press-boiled (